Prevention of hormonal breast cancer by dietary jamun. Issue 6 (21st April 2016) - Aqil, Farrukh; Jeyabalan, Jeyaprakash; Munagala, Radha; Singh, Inder Pal; Gupta, Ramesh C.
Abstract : Syzygium cumini (jamun) has the diversity of anthocyanidins of blueberry and bilberry and the abundance of ellagitannins/ellagic acid of black raspberry. These chemopreventives from jamun effectively inhibit breast cancer tumorigenesis induced by 17β‐estrogen in ACI rats modulating various genes and miRNAs. Abstract : Scope: Syzygium cumini (jamun) is perhaps the only berry that has the diversity of anthocyanidins of blueberry and bilberry and the abundance of ellagitannins/ellagic acid of black raspberry. Here, we report the potential of jamun against 17β‐estrogen‐mediated breast cancer and the role of miRNAs and other targets in disease inhibition. Methods and results: Female August‐Copenhagen Irish rats were given AIN‐93M diet or diet supplemented with jamun. Two weeks later, animals received 17β‐estradiol and were palpated weekly for the mammary tumors. At the end of 26 weeks, the jamun‐diet significantly delayed the first tumor appearance by 21 days, and reduced the tumor incidence (65% versus 96%), tumor burden (313 ± 95 versus 661 ± 123 mm 3 ) and tumor multiplicity (1.8 ± 0.3 versus 4.2 ± 0.4 tumors/rat) compared to control. The experimental diet significantly reduced the estrogen‐associated growth of pituitary prolactinomas, circulating prolactin and estradiol levels and offset estrogen‐associated increases in mammary cell‐proliferation, estrogen receptor‐alpha (ER‐α), and cyclinD1. miRNAs that were either overexpressed (miR‐182 and miR‐375) or underexpressed (miR‐127 and miR‐206) following estrogen‐treatment were significantly protected by jamun diet. Conclusions: Together, our data show that jamun significantly offset estrogen‐mediated alterations in mammary cell‐proliferation, ER‐α, cyclinD1, and candidate miRNAs, and that the modulation of these biomarkers correlated with a reduction in mammary carcinogenicity.